2014
DOI: 10.1111/hex.12268
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative insight of HIV/AIDS patients' perspective on disease and disclosure

Abstract: Background Understanding patients' knowledge and belief towards disease could play a vital role from an outcome perspective of disease management and HIV/AIDS patients are not exception to that.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
1
15
1
3
Order By: Relevance
“…However, other studies have demonstrated a direct correlation between adherence and viral load suppression [46,47]. Nilsson et al had a relatively larger sample size than our study (144 patients) [39], while Li et al followed their patients beyond 18 months [40]. We think our different study findings can be ascribed to the methodological differences in the length of patient follow-up between the cited studies and the current study.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…However, other studies have demonstrated a direct correlation between adherence and viral load suppression [46,47]. Nilsson et al had a relatively larger sample size than our study (144 patients) [39], while Li et al followed their patients beyond 18 months [40]. We think our different study findings can be ascribed to the methodological differences in the length of patient follow-up between the cited studies and the current study.…”
contrasting
confidence: 63%
“…Syed et al reported disease non-disclosure to be associated with fear of stigma and family emotions [39]. HIV/AIDS stigma, in particular, poses a major barrier to disclosure [40].…”
mentioning
confidence: 99%
“…HIV patients have to cope with the fear of stigma and discrimination [93]. HIV-positive women are particularly vulnerable to rejection and the loss of important familial and social relationships [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Mencoba menghilang dari peredaran dunia akan merasa bahwa ia mendapat penyakit yang mengancam hidupnya. Hal itu dikarenakan adanya penurunan daya tahan tubuh 7 . Berdasarkan Oskouie et.al 7 penderita HIV tidak memahami secara tentang penyakit tersebut.…”
Section: "Kalau Tentang Penyakit Itu Saya Tahu Tapi Kan Dulunya Kalaunclassified
“…Hal itu dikarenakan adanya penurunan daya tahan tubuh 7 . Berdasarkan Oskouie et.al 7 penderita HIV tidak memahami secara tentang penyakit tersebut. Mereka hanya beranggapan bahwa penyakit tersebut penyebab kematiannya.…”
Section: "Kalau Tentang Penyakit Itu Saya Tahu Tapi Kan Dulunya Kalaunclassified